Psychometric Evaluation of the Ukrainian Version of the Hogg Eco-Anxiety Scale (HEAS-UA) - Kryazh , Iryna; Baranov , Vladyslav (Insight: the psychological dimensions of society, 2025)
The aim of the study was a psychometric evaluation of the first Ukrainian-language version of the Hogg Eco-Anxiety Scale (HEAS) with subsequent comparative analysis of eco-anxiety indicators in different gender and age groups. The HEAS (Hogg et al., 2021) is a questionnaire consisting of 13 items. It measures eco-anxiety as four types of psychological responses to the modern ecological crisis: affective symptoms, rumination, behavioral symptoms, and anxiety about personal impact. The factor structure of the HEAS-UA, internal convergent and discriminant validity, composite reliability, internal consistency, measurement invariance, and concurrent validity were assessed. Methods. A direct and reverse translation of the English-language scale was conducted for the creation of the Ukrainian version of the HEAS. Via the online service, Google Forms, 446 Ukrainians (67.9% female, age M = 32.3, SD = 11.04) completed the HEAS-UA along with scales measuring depression, positive and negative affect, life satisfaction, pro-environmental behavior in the social sphere, climate change denial, and environmental self-efficacy. The data were analyzed using the statistical software JASP. The research results confirmed the superior fit of the four-factor model to the empirical data compared to other models: the second-order factor model, the bifactor model, and the one-factor model. High internal consistency of each subscale was established, and measurement invariance was confirmed across gender and age groups. Weak to moderate correlations were found between the eco-anxiety subscales and indicators of depression, subjective well-being, pro-environmental behavior, attitudes toward change climate, and environmental self-efficacy, supporting the concurrent validity of the HEAS-UA. Small effects of differences in eco-anxiety levels between men and women, as well as between young and middle-aged individuals, were identified. Young people and women exhibited higher levels of anxiety about their impact, with women also displaying more pronounced affective symptoms. Discussion and conclusions. The HEAS-UA is a valid and reliable instrument that can be effectively used to measure eco-anxiety in Ukrainian-speaking populations, particularly in cross-cultural studies.
Keywords: Array; Array; Array; Array; Array; Array; Array